The Local Wisdom-Based E-Comic to Enhance Fifth Grade Elementary Students’ Understanding of Regional Economic Concepts in Tulungagung Regency - Primadita, Adea Hayyu; Suja’i, Imam Sukwatus; Rindrayani, Sulastri Rini (Sumber Belajar Sejahtera, 2025)
This study was conducted to develop a local wisdom-based E-comic as a learning medium that aimed at improving the understanding of regional economic concepts among fifth-grade elementary school students. The study was motivated by the low level of students’ comprehension regarding regional economic material and the limited availability of engaging and contextual learning media. The ADDIE development model was employed in this research. The product was designed in the form of a digital comic that features interactive visual narratives, with content focused on regional economic themes integrated with the local wisdom of Tulungagung Regency—such as economic activities, leading local products, and the potential of the creative economy. The research was carried out with fifth-grade students from State Elementary School 2 of Pucung Kidul, Tulungagung as participants. Data were collected through observations, questionnaires, interviews, document analysis, and concept comprehension tests. The e-comic was validated by media and content experts, and it was found to be highly valid and appropriate for use. Positive responses were obtained from both teachers and students, indicating that the e-comic was considered feasible and practical for learning purposes. Small-scale and large-scale trials were conducted, and the results showed that students’ conceptual understanding was significantly improved through the use of the local wisdom-based e-comic, as supported by the analysis of a paired sample t-test. To sum up, the developed e-comic was proven to be valid, practical, and effective in enhancing the understanding of regional economic concepts among fifth-grade elementary students.